Group techniques - Corey, Gerald; Corey, Marianne Schneider; Callanan, Patrick; Russell, J. Michael (Brooks/Cole, Cengage Learning, 2015)
"More than a recipe book of techniques that group leaders can pull out at the right time, this book encourages readers to use techniques sensitively and creatively in their own groups, and to go one step further to invent their own techniques. The authors draw on their combined experiences as teachers, as consultants to mental-health professionals, and as private practitioners to provide a realistic approach to group work. Emphasizing that techniques are means, not ends, the book is designed to enhance the group leader's ability to generate a therapeutic and human rapport between leader and members."--Publisher's website.